Effect of Barrier Height on the Design of Stepped Spillway Using Smoothed Particle Hydrodynamics and Particle Image Velocimetry - Azman A.; Ng F.C.; Zawawi M.H.; Abas A.; Rozainy M. A. Z M.R.; Abustan I.; Adlan M.N.; Tam W.L. (Springer Verlag, 2023)
Air entrainment; Efficiency; Flow of water; Flow patterns; Flow visualization; Hydraulics; Oxygenation; Spillways; Velocimeters; Velocity measurement; Water aeration; Aeration effect; Aeration efficiencies; Barrier heights; Lower pressures; Particle image velocimetries; Smoothed particle hydrodynamics; State of the art; Stepped spillways; Hydrodynamics